How to raise pigs : everything you need to know : breed guide & selection, proper care & healthy feeding, building facilities and fencing, showing advice /: everything you need to know : breed guide & selection, proper care & healthy feeding, building facilities and fencing, showing advice. (2008) - Unknown
No abstract available